2020
DOI: 10.1177/0300985820906891
|View full text |Cite
|
Sign up to set email alerts
|

Severe Degenerative Changes in Cryptorchid Testes in Japanese Black Cattle

Abstract: This is a histopathologic and endocrinologic study of 6 calves diagnosed with cryptorchidism. Cases 1–3 were diagnosed as resembling testicular regression syndrome. In cases 1 and 2, the extracted tissue was a small, firm, gray-white mass, and there was lack of obvious testicular tissue in case 3. Histopathologically, the excised tissue in cases 1–3 was a fibrotic testicular remnant with inflammation, mineralization, hemosiderin-laden macrophages or lipofuscin-laden macrophages, and lack of germ cells and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…In this study, greater interstitial volumes were consistently observed in the cryptorchid testes compared to the other groups. Our findings are consistent with a previous study on cryptorchid calves in which the hypoplastic cryptorchid testes presented an increased number of interstitial endocrine cells, marked fibrosis, and arrested spermatogenesis [40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, greater interstitial volumes were consistently observed in the cryptorchid testes compared to the other groups. Our findings are consistent with a previous study on cryptorchid calves in which the hypoplastic cryptorchid testes presented an increased number of interstitial endocrine cells, marked fibrosis, and arrested spermatogenesis [40].…”
Section: Discussionsupporting
confidence: 93%
“…The testes of five rats in each group were removed at designated time points (40,63, and 90 days after birth) [19]. The rats were euthanized by cervical dislocation at each of the three time points, the testes were excised, and sperm analysis and stereology were undertaken to determine various parameters.…”
Section: Induction Of Cryptorchidismmentioning
confidence: 99%